PELAKSANAAN PELAYANAN PUBLIK DI SEKRETARIAT DAERAH KABUPATEN KUTAI BARAT (STUDY TENTANG PENGGUNAAN BAHAN BAKAR MINYAK PADA BAGIAN UMUM DI SEKRETARIAT DAERAH KABUPATEN KUTAI BARAT ) - Harly Lionard; Aji Ratna Kusuma; Muhammad Noor (Magister Administrasi Publik FISIP Universitas Mulawarman, 2017)
The purpose of this study is to analyse and describe the implementation of public services at the Regional Secretariat about the use of fuel oil to the service in the General section. This research is a quantitative descriptive research and using statistical analysis techniques.